Environmental Caring Through Character Education In Vocational School - Lusy Tunik Muharlisiani; Yoyok Soesatyo; Amrozi Khamidi; Nunuk Hariyati; Siti Bariroh; Endang Noerhartati; Johny Sugiono; Citrawati Jatiningrum (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This research aims to describe the character of environmental awareness of character education and finding model of the development of character strengthening. Design/methodology/approach: This method uses descriptive qualitative, data collection by in-depth interviews, surveys, observations, and documentation by observing the development of the character of environment. The data sources are principals, teachers, students, and parents. Efforts can be made by playing methods included in the curriculum for local content such as Ethics and Introduction to the Environment. The nature of concern for the environment will be increasingly imprinted if in addition to education at school while at home, parents of students also motivate, give advice and role models to care for the environment and will be more effective when collaborated formal and informal education. The data validity technique uses technique and source triangulation through data display, data reduction, and conclusion drawing. Finding: The results are 1) the development of the school curriculum includes self-development programs, integration in subjects, and school culture (school local content, living drug stores, parks, spaces and offices, inspiration to understudies, use of endowments and disciplines, and character advancement, caring , and Responsibility); 2) Input from stakeholders to strengthen environmental care character education for students; 3) The model of developing character of environmental care in vocational students. Research limitations/implications: Result of this research can be used as references to increase environmental caring through character education in vocational school Practical implications: The conclusion that Vocational Schools have implemented character education is the presence of strategies, ideas and nature-based learning, and the availability of supporting facilities and infrastructure. Paper type: Research Paper